A THEORETICAL ASPECT OF SOCIAL ENTREPRENEURSHIP - Ratnawati; Heriani, Wiwie; Famauri, A. Tenri; Quran, Habibul; Quran, M. Yusuf; Quran, A. Bustam (International Journal of Psychosocial Rehabilitation, 2020)
Serial killers is a very troubling and harming many people becauses one’s life does not mean anything in front of the perpetrator, in fact, life is basic right for everyone. One of the most famous serial killer cases is Jack the Ripper case who has taken 440 people live. This incident can be influenced by various factor which come from external or internal factors from the inside. The problem aspect will be explore in this paper is what is the factors a person committed a crime? This research is a socio-legal using statute and case approach, data collected then will analyzed qualitatively. The result of the research show that is enviromental factor and mental is two dominant its afecting someone to doing a serial killers.Keywords:,